Test of Acceptance and Iron Content of Baymor “Red Spinach & Moringa” as a Treat to Prevent Anemia in Adolescent Women - Anisah Rona Rosyidah; Juliana Christiyaningsih; Nuning Marina Pengge; Nur Hatijah (Politeknik Kesehatan Kemenkes Surabaya, 2023)
Based on DP3AK 2021 East Java, 23% of young women and 12% of young men suffer from anemia. Red spinach and Moringa leaves are contain high levels of iron so it can be used as alternative foods to prevent anemia in young women. The purpose was to analyze the results of tests of acceptability and iron levels of